Prevalence of respiratory symptoms among cement workers at Ipoh, Perak, Malaysia - Aananandha Rav Naidu, Perakas Rav (2022)
The respiratory system is the cement industry's most weak organ. Air pollution, with a range of health consequences, known to cause major public health issues. Few studies have been carried out on acute effects of cement dust exposure on Occupational Health and Safety of the workers. The objective of this study is to determine the prevalence of occupational safety and health among cement workers using lung functions test in Ipoh, Perak. This study is conducted to investigate the associations between current "total" dust exposure and acute respiratory symptoms and lung function among cement factory workers. This study was conducted in a cement factory in Ipoh, Perak. A total of 104 workers involved in this study. This study design is cross-sectional study utilising the quantitative method and polling sampling method was utilised to sample the respondents based on the inclusion criteria in order to measure the particulate matter from different work stations (raw material, kiln and packing), respiratory symptoms data and lung function test. The data were obtained by a set of questionnaire adapted from the European Community Respiratory Health Survey II (EC-RHS II, 2014), spirometer and DustTrak. Kiln workstation recorded the highest distribution of lung function abnormalities. Meanwhile, the highest reading of dust measurements is in the packing (0.44 mg/m3). This is due to the work process in this work station which generated high volume of dust. The correlation between the dust exposure and lung function, FVC and FEV1 showed significant relationship with the exposure of dust with value of (r = -0.307, p-value = 0.002) and (r = -0.270, p-value = 0.006) respectively. Most significant symptoms reported by the workers was coughing in the morning (pvalue = 0.044). The comparison of lung function between all work station, FVC and FEV1 shows statistical differences among work station with the value of (z = 9.568, p-value = 0.008) and (z = 7.769, p-value = 0.021) respectively. Majority of the workers had respiratory symptoms of shortness of breath. The highest number of workers that exposed to the dust was workers from the kiln work station. To conclude, there is a prevalence of occupational safety and health among cement workers using lung functions test in Ipoh, Perak. This study shows that respiratory problems are associated with exposure to cement dust. Exposure to high concentration of cement dust in the cement manufacturing facility is associated with the decrease in the lung function of the workers. The exposure of dust also found to be responsible for the increased prevalence of respiratory symptoms towards of the respondents. Personal monitoring using compact, battery-powered equipment allows for the assessment of an individual's exposure while they go about their everyday activities. Personal monitoring can significantly minimise misclassification of exposure and increase the ability to find associations between particle pollution and negative health consequences Also, cement dust exposure could be decreased by using wet or dry dust reduction engineering controls, enclosed cabs, and implementing a dust control program. Furthermore, this research can be used as a baseline for the core business. It is also critical for management to arrange with specialists such as Occupational Health Doctors (OHD) for a thorough medical examination and frequent lung function tests more frequently for their workers.